Brain Antigens Stimulate Proliferation of T Lymphocytes With a Pathogenic Phenotype in Multiple Sclerosis Patients - Gottlieb, Assaf; Pham, Hoai Phuong T.; Lindsey, John William (Frontiers in Immunology, 2022)
A method to stimulate T lymphocytes with a broad range of brain antigens would facilitate identification of the autoantigens for multiple sclerosis and enable definition of the pathogenic mechanisms important for multiple sclerosis. In a previous work, we found that the obvious approach of culturing leukocytes with homogenized brain tissue does not work because the brain homogenate suppresses antigen-specific lymphocyte proliferation. We now report a method that substantially reduces the suppressive activity. We used this non-suppressive brain homogenate to stimulate leukocytes from multiple sclerosis patients and controls. We also stimulated with common viruses for comparison. We measured proliferation, selected the responding CD3+ cells with flow cytometry, and sequenced their transcriptomes for mRNA and T-cell receptor sequences. The mRNA expression suggested that the brain-responding cells from MS patients are potentially pathogenic. The T-cell receptor repertoire of the brain-responding cells was clonal with minimal overlap with virus antigens.